Economic implications from deficit finance - Stevan Gaber (Bamberg University, Bamberg Economic Research Group on Government and Growth (BERG), 2010)
The paper enlightens popular part of the budget policy - deficit finance. In the process of securing economic conditions to surpass the current economic crises, the governments all over the world incline towards debt deficit finance. The intention is to describe the implications such as multiplier effect, crowding out effect, correlation between budget and trade deficit. One of them are positive, they increase the aggregate demand and national income, other negative in term that they crowd out the private sector from the capital market under increased demand for loanable funds.
Keywords: H30; H62; H63; 330; Budget deficit; Crowding out; Twin deficits; Exchange rates; Haushaltsdefizit; Öffentliche Schulden; Multiplikator; Crowding out; Zahlungsbilanzungleichgewicht; Wechselkurs